Acute symptomatic seizures and status epilepticus in older adults: A narrative review focusing on management and outcomes - Kong, Wan Yee; Marawar, Rohit (Frontiers in Neurology, 2022)
A clear narrative of acute symptomatic seizures (ASyS) in older adults is lacking. Older adults (≥ 60 years) have the highest incidence of seizures of all age groups and necessitate a tailored approach. ASyS has a bimodal peak in infancy and older age (82.3-123.2/100,000/year after age 65). ASyS can represent half of the new-onset seizures in older adults and can progress to ASySE in 52-72% of the patients. Common etiologies for ASyS in older adults include acute stroke and metabolic disturbances. For ASySE, common etiologies are acute stroke and anoxic brain injury. Initial testing for ASyS should be consistent with the most common and urgent etiologies. 20-minute EEG is less sensitive in older adults than younger adults and might not help predict chronic epilepsy. The prolonged post-ictal phase is an additional challenge for acute management. 30% of older adults with ASyS subsequently develop epilepsy. The risk of wrongly equating ASyS as the first seizure of epilepsy is higher in an older adult due to the increased long-term challenges with chronic anti-seizure medication (ASM) treatment. Specific challenges to managing ASyS in older adults are related to their chronic comorbidities and polypharmacy. It is unclear if the prognosis of ASyS is dependent on the underlying etiology. Short-term mortality is 1.6 to 3.6 times higher than younger adults. ASySE has high short-term mortality, especially when it is secondary to acute stroke. An acute symptomatic etiology of ASySE had five times increased risk of short-term mortality compared to other types of etiology.